Simplifying four-strand flexor tendon repair using double-stranded suture: a comparative ex vivo study on tensile strength and bulking - Low, T.H.; Ahmad, Tunku Sara; Ng, E.S. (SAGE Publications (UK and US), 2012)

(untitled)
We have compared a simple four-strand flexor tendon repair, the single cross-stitch locked repair using a double-stranded suture (dsSCL) against two other four-strand repairs: the Pennington modified Kessler with double-stranded suture (dsPMK); and the cruciate cross-stitch locked repair with single-stranded suture (Modified Sandow). Thirty fresh frozen cadaveric flexor digitorum profundus tendons were transected and repaired with one of the core repair techniques using identical suture material and reinforced with identical peripheral sutures. Bulking at the repair site and tendon-suture junctions was measured. The tendons were subjected to linear load-to-failure testing. Results showed no significant difference in ultimate tensile strength between the Modified Sandow (36.8 N) and dsSCL (32.6 N) whereas the dsPMK was significantly weaker (26.8 N). There were no significant differences in 2 mm gap force, stiffness or bulk between the three repairs. We concluded that the simpler dsSCL repair is comparable to the modified Sandow repair in tensile strength, stiffness and bulking.